1993
DOI: 10.1113/jphysiol.1993.sp019857
|View full text |Cite
|
Sign up to set email alerts
|

Uniform olivocerebellar conduction time underlies Purkinje cell complex spike synchronicity in the rat cerebellum.

Abstract: 3. Multiple-electrode recording of spontaneous Purkinje cell CS activity was employed to study the spatial extent of CS synchronicity in the cerebellar cortex. Recordings of CS were obtained from Purkinje cells located on the surface and along the walls of lobule crus 2a. The rostrocaudal band-like distribution of simultaneous (within 1 ms) CS activity in Purkinje cells extended down the sides of the cerebellar folia to the deepest areas recorded (1-6-2-6 mm deep). As shown in previous experiments, the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
181
6
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(203 citation statements)
references
References 36 publications
15
181
6
1
Order By: Relevance
“…Synchrony has also been observed in conduction time measurements of complex spikes evoked by stimulating olivocerebellar axons near the IO (Sugihara et al 1993). However, measurements of small conduction times and estimates of small conduction distances in highly foliated mammalian Cb resulted in disagreement as to whether the olivocerebellar conduction time is uniform (Aggelopulos et al 1995;Baker and Edgley 2006a; also see rebuttal by Baker and Edgley 2006b and response by Lang et al 2006).…”
Section: Using the Turtle As A Model System To Study Olivocerebellar mentioning
confidence: 91%
See 1 more Smart Citation
“…Synchrony has also been observed in conduction time measurements of complex spikes evoked by stimulating olivocerebellar axons near the IO (Sugihara et al 1993). However, measurements of small conduction times and estimates of small conduction distances in highly foliated mammalian Cb resulted in disagreement as to whether the olivocerebellar conduction time is uniform (Aggelopulos et al 1995;Baker and Edgley 2006a; also see rebuttal by Baker and Edgley 2006b and response by Lang et al 2006).…”
Section: Using the Turtle As A Model System To Study Olivocerebellar mentioning
confidence: 91%
“…It has three layers overlying white matter whose sole output neurons, Purkinje cells (PCs), are excited by the ascending axons of the granule cells (Cohen and Yarom 1998;Huang et al 2006;Isope and Barbour 2002;Tolbert et al 2004), parallel fibers (Eccles et al 1966b), and climbing fibers (Eccles et al 1966a), which carry signals from the contralateral inferior olive (IO) (Dow 1942). Recent hypotheses have focused on Cb's role in behavioral timing (Kistler et al 2000;Kitazawa and Wolpert 2005;Xu et al 2006;Yarom and Cohen 2002), although controversy surrounds reports that olivocerebellar responses (Sugihara et al 1993) are synchronous (see Aggelopulos et al 1995;Baker and Edgley 2006a,b and the responses of Lang et al 2006). One approach to understand the timing of physiological responses of Cb has been to record multiple responses, first performed on about 2 mm 2 of turtle Cb (8 ϫ 8 electrode array recording extracellular fields; Bantli 1972).…”
Section: Introductionmentioning
confidence: 99%
“…To preserve the precise synchronization present at the IO level, the conduction time to the different parts of the cerebellum must be relatively invariant despite differences in path length. This is indeed the case in the adult rat (Sugihara et al 1993); however, whether this invariance holds for larger animals has been questioned (Aggelopoulos et al 1995), although even in the latter study the latency of CS activity evoked by IO stimuli varied by only several milliseconds.A previous study identified two mechanisms that the olivocerebellar system uses to achieve a uniform conduction time throughout the cerebellar cortex (Sugihara et al 1993). First, the diameter of an olivocerebellar axon was found to vary with its projection distance.…”
mentioning
confidence: 84%
“…Indeed, the density of neuronal gap junctions appears to be higher in the IO than in any other CNS region (Belluardo et al 2000;Condorelli et al 1998;De Zeeuw et al 1995). This coupling allows IO neurons to generate precisely (on a millisecond time scale) synchronized activity that results in simultaneous complex spike (CS) activity in the cerebellum (Lang et al 1999;Sasaki et al 1989;Sugihara et al 1993;Yamamoto et al 2001).Maintenance of the synchronization present in IO discharges presents a challenge for the olivocerebellar system because the length of the olivocerebellar pathway to different points on the cerebellar cortex varies. In rats, there can be more than a twofold difference in the length of the olivocerebellar projection to different regions of the cortex (Sugihara et al 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation